Predicting and Moderating COVID-Fear and Stress among College Students in Argentina and the USA - Rice, Kenneth G. (2023)
The COVID-19 pandemic negatively affected mental health worldwide and college students were particularly vulnerable to its adverse effects. This longitudinal study was designed to highlight and compare the COVID experiences of college students in Argentina and the USA (N = 361). Specifically, we examined individual factors (gender, emotional regulation, and social support) assessed prior to the pandemic for their role as predictors or moderators of COVID-fear and psychological stress during the first months of the pandemic. The results supported measurement invariance for brief measures of COVID-fear and indicated that, overall, COVID-fear was highest during the second wave of the study (March–April 2020), lowest during the third wave (June 2020), and then rose again during the fourth wave (September 2020). Several interaction effects emerged, revealing important country-level differences in COVID-fear effects for the emotion regulation and social support factors. More so in the Argentina sample than in the USA sample, higher levels of social support at Time 1 were associated with increases in the effect of COVID-fear on stress among students. We discussed the implications of these and other findings for future cross-cultural pandemic-related stress studies.